Ethnobotanic of Pest Preventing Plants Oryza sativa L. by The Baduy Tribe Community in Leuwidamar District, Lebak Banten, Indonesia - Alwi, Akhmad Bashori; Minarno, Eko Budi; Rahmah, Azizatur; Shonhaji, Achmad; Adawiyah, Robiatul (El-Hayah : Jurnal Biologi, 2020)
Baduy people have local wisdom about the use of plants, among others, as ingredients to prevent the presence of rice pests (Oryza sativa L.). the importance of these pest-preventing plants to produce allelopathy in order to prevent rice pests (Oryza sativa L.). To find out what plants are used by Baduy people, this research is necessary. Exploration of pest control plants is carried out using the PEA (Participatory Ethnobotanical Appraisal) approach, besides that it also uses survey methods and open interview techniques. The results of the survey were 21 non-key informants and 5 key-informants from the Outer Baduy community and 12 non-key informants and 1 key informant from the Inner Baduy community, 35 species from 22 plant families were used in all rituals to prevent the presence of rice pests. . Plants that have similarities in usage by the Outer Baduy and Inner Baduy are Bamboo Wuluh leaves (Schyzostachyum iraten), Noni leaves (Morinda citrifolia), Bemban (Donax canniformis), Walang leaves (Achasma walang Val.) And Langge leaves (Homalomena cordata) . The percentages of plant organs used to prevent the presence of rice pests are leaves (77%), stems (17%) and fruit (6%). The method of processing plants as raw material for rice pest prevention ingredients is to cut them in small volumes / chop (39.74%), pound (52.56%), ferment (3.85%) and burn (3.85%). Baduy rituals in preventing the presence of rice pests include 5 types namely Ngubaran Samara Pungpuhunan ("Treatment" of Main Plants), Ngubaran Cangkudu ("Treatment" of Noni), Ngubaran Bangban ("Treatment" of Bemban / Donax canniformis), Fumigation, and Leuit Susumpingan (Lumbung offerings)